Os psicólogos nas unidades de saúde : uma investigação acerca de alguns aspectos de sua prática profissional - Bergamin, Margareth Pereira (2010)
This dissertation proposes the study of some aspects considering the Public Health Service psychology staff s professional behavior, in order to comprehend the common practices adopted by these professionals in the Healthcare Unities and the way they bond the acquired academic knowledge with the professional performance. This object of study reveals a fundamental importance due to the recent insertion of this professional in the area of public health and the currently expansion in contracts of psychologists for the Public Health Service a well different panorama of this profession in Brazil, when the performance of the psychologists were priority in the organizational and clinical area. The results of this research point some of the ways that have been trailed by psychologists until now, contributing, therefore, to a critical analysis of the performance of these professionals